Cultural Improvement of the Gen-Z Digital Media User in Pinge Village Bali - Melati Mediana Tobing; Leonard Hutabarat; Aprina Jovanka Sirait (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The intensity of digital media use among Generation Z (Gen-Z) has spread to Pinge Traditional Village in Tabanan Regency, Bali. This study aims to determine the effect of intensive use of social media by students of SMP 3 Marga in Pinge Village, Bali on their interest in learning local culture and ability to interpret local culture amid the influx of cultural information in the world. A survey of 115 Gen Z respondents who are active users of social media at SMP 3 Marga showed a change in attitude towards increasing local cultural loyalty through a correlation test of 0.881 and it can be concluded that the results of (Intensity of Gen-Z Social Media Use) have a positive value with a large relationship of 0.638 (coefficient test) which can be categorized as having a fairly strong degree of relationship to (Meaning of Balinese Local Culture). This research provides an overview of the positive impact of social media on the understanding of local culture. There is a big role of parents at home and in the Pinge Village complex in maintaining village children on every cultural and religious occasion that is routinely held. Through this research, it can be predicted that the future picture of Balinese culture will continue to be preserved until the current generation Z becomes adults in the future. However, hypothesis testing explains that the presence of information technology will result in a change in the meaning of culture in Pinge Village by Gen Z in a positive direction.